2023
DOI: 10.3390/su16010234
|View full text |Cite
|
Sign up to set email alerts
|

Exploring How and When Environmental Corporate Social Responsibility Impacts Employees’ Green Innovative Work Behavior: The Mediating Role of Creative Self-Efficacy and Environmental Commitment

Jiali Chen,
Aiqing Zhang

Abstract: While prior research has recognized the significance of employees’ green innovative work behavior (GIWB) for organizational sustainability, few studies have explored how to effectively promote such behavior. Following the stimulus-organism-response (S-O-R) framework, we investigate how and when environmental corporate social responsibility (ECSR) drives employees’ GIWB. We conducted a two-wave lagged data analysis with 300 Chinese manufacturing employees. Our results reveal that creative self-efficacy and envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 101 publications
0
1
0
Order By: Relevance
“…Yu Lijing et al (2018) pointed out that green innovation is an effective way for logistics enterprises to maintain a competitive advantage, and government participation in supervision is a booster of green innovation diffusion in logistics enterprises [2]. Chen and Zhang (2024) pointed out that, in order to cope with environmental challenges, the Chinese government encouraged enterprises to abide by corporate social responsibility, which made many enterprises gradually adopt cleaner production practices [3]. Han and Yang (2022) analyzed the interest game behavior between two typical target companies and a government, and found that the role of the government is embodied in guiding and motivating, such as guiding the alliance team to standardize the internal system and encouraging the restraint mechanism.…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…Yu Lijing et al (2018) pointed out that green innovation is an effective way for logistics enterprises to maintain a competitive advantage, and government participation in supervision is a booster of green innovation diffusion in logistics enterprises [2]. Chen and Zhang (2024) pointed out that, in order to cope with environmental challenges, the Chinese government encouraged enterprises to abide by corporate social responsibility, which made many enterprises gradually adopt cleaner production practices [3]. Han and Yang (2022) analyzed the interest game behavior between two typical target companies and a government, and found that the role of the government is embodied in guiding and motivating, such as guiding the alliance team to standardize the internal system and encouraging the restraint mechanism.…”
Section: Theoretical Developmentmentioning
confidence: 99%